Elaboration on Public Administration Crises: An Endeavor in Seeking Scientifc Identity - Iwan Tanjung Sutarna; Khuriyatul Husna; Paramita Iswari (Policy & Governance Review, 2017)
This paper aims to elaborate the crises occurring in the science of public administration based on signifcant conceptions of scholars. Public administration’s initial emergence as a novel scientifc discipline sparked a theoretical-conceptual debate specifcally in the domain of epistemology. For the sake of systematical order, this paper is divided into three phases of crisis based on the dynamics of the theoretical-conceptual development of public administration, namely: (1) identity crisis; (2) paradigm crisis; and (3) intellectual crisis. The illustration of each crisis phase is aimed at conveying conception points of scientists which facilitates in reading the narrative of shifts and theoretical-conceptual contents including their inherent values. For this reason, a search or walkthrough of relevant literature is necessary to observe the development of thoughts in public administration.The study result shows that the diﬀering ideas and argumentations which had occurred throughout every discussion on public administration have had implications on the heterogeneity of the public administration feld. The various shifts of locus-focus and paradigm in public administration is seen as a systematic atempt in fnding its true self as a scientifc discipline. The eﬀorts of public administration in separating itself from the shadows of political science was also observed, although being capable of truly separating itself is considered as extremely difcult, bearing in mind that the focus and locus of public administration is very much aﬀected by constantly developing social political inﬂuences. In addition to that, various shifts of locus and focus seems to have empirical implications particularly in the scientifc scope of public administration.